Eletrodo de ouro nanoporoso como um sensor eletroquímico para detecção do contaminante emergente 2,6-dicloro-1,4-benzoquinona em amostras de água. - OLIVEIRA JUNIOR, José Antonio de (2021)
Some compound are formed during wastewater disinfection process, especially 2,6-dichloro 1,4-benzoquinone (2,6-DCBQ), which belongs to halobenzoquinones. Reports associate this compound with cases of cancer and various other harmful effects on the endocrine system. In this work, the potential of using a nanoporous gold film as an electrochemical sensor for voltammetric detection of 2,6-DCBQ was investigated. Forming the nanoporous structure consists of a method proposed in the literature in three electrochemical steps, taking a simple, fast and efficient modification route. The formation time of the nanoporous film to obtain the modified electrode was investigated, being established as the optimal time 15 min. An insight into the effects of the anodizing/reduction process on the performance of a nanoporous gold electrocatalyst in an acidic medium was provided. The electrode was analyzed in a 3-stage modification by SEM and AFM. Subsequently, the performance of the electrochemical sensor in detecting 2,6-dichloro-1,4-benzoquinone (2,6-DCBQ) was evaluated. An electrocatalytic effect could be noted due to an increase in anodic faradaic peak current of 232,56% and an 80 mV decrease in anodic peak potential compared to the unmodified electrode. Studies after the dependence of the peak current of the analyte with pH variation, better sensitivity at pH = 5.00. The kinetics of the redox reaction is diffusion controlled, with two electrons being transferred in it. In addition, it was found that the oxidation of 2,6-DCBQ has the same number of protons and electrons generated in the reaction (2 e- / 2 H+ ). The supporting electrolyte showed the most efficiency among tested in the citrate buffer 0.1 mol L-1 results. In view of the system's reversibility, square wave voltammetry showed best analytical signal, the optimized technique parameters were: Eamplitude = 80 mV; Estep = 10mV and Frequency = 25Hz. After the optimization of the entire process, a remarkable performance in the detection of 2,6-DCBQ was obtained. The detection limit, quantification limit and sensitivity were 0,77 µmol L−1 , 2,56 µmol L −1 and 0,64 µA µmol L−1 , respectively. With this, the technique was applied to determine of 2,6-DCBQ in treated water samples (deionized and tap) collected in the electrochemical laboratory (LELQ) at the Federal University of Maranhão campus. The recovery test performed in deionized water and tap water showed recovery values range from 98.80% to 108.70%. These data showed that the optimized system is robust, sensitive, capable of substrate detection with no/low matrix interferences, and suitable for detection applications in treated water samples.